Interventions to reduce vasovagal reactions in blood donors: a systematic review and meta‐analysis. Issue 1 (February 2016) - Fisher, S. A.; Allen, D.; Dorée, C.; Naylor, J.; Angelantonio, E. Di; Roberts, D. J.
SUMMARY: Vasovagal reactions (VVRs) in blood donors have significant implications for the welfare of donors, donor retention and the management of donor sessions. We present a systematic review of interventions designed to prevent or reduce VVRs in blood donors. Electronic databases were searched for eligible randomised trials to March 2015. Data on study design and outcomes were extracted and pooled using random effects meta‐analyses. Sixteen trials met the inclusion criteria: five trials (12 042 participants) of pre‐donation water, eight trials (3500 participants) of applied muscle tension (AMT) and one trial each of AMT combined with water, caffeine, audio‐visual distraction and/or social support. In donors receiving pre‐donation water, the relative risk (RR) compared with controls for VVRs was 0·79 [95% confidence interval (CI) 0·70–0·89, P < 0·0001] and the mean difference (MD) in severity of VVRs measured with the Blood Donation Reactions Inventory (BDRI) score was −0·32 (95% CI −0·51 to −0·12, P < 0·0001). Excluding trials with a high risk of selection bias, the RR for VVRs was 0·70 (95% CI 0·45–1·11, P = 0·13). In donors who received AMT, there was no difference in the risk of chair recline in response to donor distress from controls (RR 0·76, 95% CI 0·53–1·10, P = 0·15), although the MD in BDRI score was −0·07 (95% CI −0·11 to −0·03, P = 0·0005). There was insufficient data to perform meta‐analysis for other interventions. Current evidence on interventions to prevent or reduce VVRs in blood donors is indeed limited and does not provide strong support for the administration of pre‐donation water or AMT during donation. Further large trials are required to reliably evaluate the effect of these and other interventions in the prevention of VVRs.